Immunoinformatic prediction of the pathogenicity of bovine viral diarrhea virus genotypes: implications for viral virulence determinants, designing novel diagnostic assays and vaccines development - Al-Kubati, Anwar A. G.; Kandeel, Mahmoud; Hussen, Jamal; Hemida, Maged Gomaa; Al-Mubarak, Abdullah I. A. (Frontiers in Veterinary Science, 2023)
BVDV significantly impacts the bovine industries. BVDV can infect various domestic and wild animals, most notably cattle. The dynamic variations among BVDV serotypes due to the continuous genetic diversity reduce the effectiveness of the currently available vaccines and the specificity/sensitivity of the diagnostic assays. Developing novel, safe, and effective vaccines against BVDV requires deep knowledge of the antigenicity and virulence of the virus. Previous studies on the antigenicity and the virulence of BVDV serotypes focused on one or a few BVDV proteins. Little is known about the orchestration of all BVDV in the context of viral virulence and immunogenicity. The current study aimed to do a comparative computational evaluation of the immunogenicity and virulence of all the encoded proteins of both BVDV1 and BVDV2. To achieve this goal, 11737 protein sequences were retrieved. The virulence prediction revealed that the NS4B proteins of both BVDV1 and 2 likely have essential roles in BVDV virulence. Similarly, both the capsid (C) and the NS4-A proteins of BVDV1 and the Npro and P7 proteins of BVDV2 are likely important virulent factors. There was a clear trend of increasing predicted virulence with the progression of time in the case of BVDV1 proteins, but that was not the case for the BVDV2 proteins. Most of the proteins of the two BVDV serotypes possess antigens-predicted immunogens except Npro, P7, and NS4B. However, the predicted antigenicity of BVDV1 was significantly higher than that of BVDV2. Meanwhile, the predicted immunogenicity of the immunodominant-E2 protein has been decreasing over time. Based on our predicted antigenicity and pathogenicity studies of the two BVDV serotypes, the sub-genotypes (1a, 1f, 1k, 2a, and 2b) may represent ideal candidates for the development of future vaccines against BVDV infection in cattle. In summary, we identified some common differences between the two BVDV genotypes (BVDV1 and BVDV2) and their sub-genotypes regarding their protein antigenicity and pathogenicity. The data presented here will increase our understanding of the molecular pathogenesis of BVDV infection in cattle. It will also pave the way for developing some novel diagnostic assays/vaccines against BVDV.